Kualitas Pelayanan Rawat Jalan Loyalitas Pasien Pengguna Asuransi Swasta Terdaftar Perjanjian Waktu Temu Di RS X Jakarta Selatan - David Estrada; Mohamad Reza Hilmy; Erry Yudhya Mulyani (Syntax Corporation Indonesia, 2022)
The increasing number of hospitals in Indonesia which are managed by the government and the private sector demands to provide the maximum level of service, professionalism and competence to reflect the best service quality. Quality provides a special impetus for companies to understand customer expectations which in turn can increase customer satisfaction and create customer loyalty. This study aims to analyze the relationship between service quality and patient loyalty. Methods: This study was structured using a quantitative approach with a cross sectional method. The sample in this study were patients who had registered for an appointment at a specialist outpatient unit at the outpatient unit of RS X South Jakarta with a total of 100 people based on inclusion criteria. Data collection techniques are carried out using questionnaires or questionnaires to reveal information or data from respondents. Data analysis was performed statistically univariate and bivariate. Multivariate analysis for hypothesis testing was performed using path analysis. Data is presented in p-value and C.R. (Critical Ratio). Results: The results showed that out of 100 subjects, 60% were male, 83% had a bachelor's degree and 70% were private employees. From the bivariate analysis related to patient loyalty at the eye specialist Hospital X South Jakarta, the waiting time variable has no significant effect on the loyalty variable (CR (Critical Ratio) the value is less than 2.0 and the P value (p-value) is greater than the significance level. (α) of 0.05), the value of interpersonal communication (CR (Critical Ratio) is more than 2.0 and the P value is smaller than the significance level (α) of 0.05), employee performance (CR (Critical Ratio) is greater than 2.0 and the P value (P-Value) is smaller than the significance level (α) of 0.05, the service facility value (CR (Critical Ratio) is more than 2.0 and the P value is less than the significance level (a) of 0.05) has a positive and significant effect on the loyalty variable. Conclusion: Patient loyalty at specialist Hospital X South Jakarta is influenced by interpersonal communication, employee performance and service facilities but is not affected by waiting time.